Modeling of Investment Activity in the Development of Public-Private Partnerships in the Service Sector - Utemuratova Gulnaraxan Xojaniyazovna (American Journal of Economics and Business Management, 2023)
This article describes the investment activity of public-private partnership development in the service sector, the main structures of public-private partnership in the service sector and the main tasks of the private sector, existing barriers to successful development of public-private partnership, mechanisms for developing mutual investment instruments. criteria and principles are described. Also, the mechanism for increasing investment activity in the development of public-private partnership, the model project of public-private partnership and its preparation stages, directions for improving the mechanism for activating investment instruments for the development of public-private partnership in the service sector were studied.